Spatial transcriptomics of a parasitic flatworm provides a molecular map of drug targets and drug resistance genes - Gramberg, Svenja; Puckelwaldt, Oliver; Schmitt, Tobias; Lu, Zhigang; Haeberlein, Simone; Justus Liebig University Giessen (My University, 2024)
The spatial organization of gene expression dictates tissue functions in multicellular parasites. Here, we present the spatial transcriptome of a parasitic flatworm, the common liver fluke Fasciola hepatica. We identify gene expression profiles and marker genes for eight distinct tissues and validate the latter by in situ hybridization. To demonstrate the power of our spatial atlas, we focus on genes with substantial medical importance, including vaccine candidates (Ly6 proteins) and drug resistance genes (glutathione S-transferases, ABC transporters). Several of these genes exhibit unique expression patterns, indicating tissue-specific biological functions. Notably, the prioritization of tegumental protein kinases identifies a PKCβ, for which small-molecule targeting causes parasite death. Our comprehensive gene expression map provides unprecedented molecular insights into the organ systems of this complex parasitic organism, serving as a valuable tool for both basic and applied research.
Keywords: ddc:630